The Effect of Air Distribution System Towards Indoor Air Quality (Case Study: Auditorium of Phinisi Tower) - Yetti Yunianti Ishak; Baharuddin Hamzah; Rosady Mulyadi (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
This research aims to analyze the type of air distribution system in auditorium, the effect on air quality in the room, as well as the design of appropriate air distribution systems for the auditorium to improve air quality. This study used quantitative methods, by measuring the CO2 gas concentration, air temperature and humidity in room, using the HT-2000 data logger. The measurements were conducted when the room is empty and when the room is occupied. After that, the analysis and simulation were done by using ANSYS-Fluent software. Displacement ventilation distribution system was designed by calculating the total amount of cooling load, the required air flow rate, the air supply temperature, and the return air temperature. The analysis result showed that the mixing ventilation distribution system in the auditorium could not resolve air quality in the room. Based on that results when the room is inhabited, it was known that the lowest and highest value for CO2 concentration level was 973 ppm and 1993 ppm; for air temperature of 20.5oC and 28,6oC; while the room air humidity of 49% and 71%. The displacement ventilation distribution system was designed to overcome the air quality problem in the chamber by air temperature setting was 24oC, the air supply velocity coming from the diffuser was 0.25 m/s, the total surface area of ​​the diffuser was 20.7 m2, and the flow pattern of moving air from the bottom to top of the room.